Prevalence of obesity and associated factors among secondary school students in Slemani City Kurdistan Region, Iraq - Qadir, Muhammed Saeed; Gyanchand Rampal, Lekhraj Rampal; Mohd Sidik, Sherina; Md Said, Salmiah; Ramzi, Zhian Salah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2014)
Obesity is a well-established risk factor for cardiovascular disease. The objective of the study was to determine the prevalence of obesity and factors associated among secondary school students aged between 13 to 17 years at Slemani City Centre, Iraq. Methodology: A cross sectional study design was used. The calculated sample size was 1656. Probability proportional to size sampling technique was used to select the sample. A validated pretested questionnaire was used to collect the data. Weight and height were also taken. Data were analyzed using SPSS version 21. Chi-square test was used to determine an association between two categorical variables. Independent t-test was used to compare two means. Multiple logistic regressions were used to determine the predictors for obesity. Results: The response rate was 92.54% and the overall mean age of the 1588 respondents was 15.42 (95% CI = 15.35, 15.49) years. The prevalence of overweight and obesity was 20.6% and 11.3% respectively. Variables significantly associated with overweight and obesity (age, monthly family income, education level of parents, body part satisfaction and body size perception) were entered into the logistic regression model. Multiple logistic regression analysis showed that the predictors for overweight and obesity were age, monthly family income, body part dissatisfaction and body size perception. Conclusion: The prevalence of overweight and obesity is high (20.6% and 11.3% respectively). The predictors of obesity among secondary school students aged between 13 to 17 years old at Slemani City Centre Kurdistan Region, Iraq were age, family income and body image dissatisfaction.